THE EFFECT OF USING RETELLING TECHNIQUE ON STUDENTS’ SPEAKING SKILL AT SECOND SEMESTER OF STIE-SAK ACADEMIC YEAR 2021/2022: Sukarta Kartawijaya, S.Pd., M.Pd, Al-Padli, S.Pd., M.Pd Sekolah Tinggi Ilmu Ekonomi Sakti Alam Kerinci Email: arumisyakira@gmail.com, aalfadli425@gmail.com - Sukarta Kartawijaya Sukarta Kartawijaya; Al-Padli Al-Padli (Teaching English and Language Learning English Journal, 2022)
The objective of this research is to know whether there was any correlation between students’ speaking skill taught using retelling and taught by using conventional technique. The type of this research used experimental research. The quasi-experimental design which used here was nonequivalent control group Design. The designs include both experimental group and a control group, but subjects are not randomly assigned. In these designs, first, the experimental group and the control group were given a pretest, then after the treatment each of the groups were given a posttest. It was done with two classes which taught using retelling technique and another class taught using conventional strategy. In collecting the data, the data in this research was speaking test. Test was used to measure the ability of students. In this research the test was speaking test to see the comprehension of students in retelling in speaking. The population of the research was all of the second semester of STIE-SAK academic year 2021/2022. There were two classes at second semester of STIE-SAK on accountant major. In analyzing the data, the researcher calculated and analyzed all of data. From the data analysis, the result of test shows that there is a significant difference of the students’ achievement taught using retelling rather than the students’ achievement who was not taught using retelling. The mean of students’ scores in experimental group is 73,36 and in the control group is 67,58. There was difference between two classes from t-test result than t-table, tcount= 0,35 > ttable= 0.05. It was also supported by the mean scores gained by the students. The students’ mean score for the students who were taught using retelling were higher than the students’ mean scores who were not taught using retelling, it was 73,36 for experiment class and 67,58 for control class. It means that the mean of the students score in experimental group is higher than in control group. The results of hypothesis testing also proved that the using of retelling technique is better than the using of conventional strategy in teaching speaking.